Manufacturing Production and Non-Agricultural Employment rate in South Africa: Time Series Analysis - Muzindutsi, Paul-Francois (Journal of Economics and Behavioral Studies, 2014)
South African is faced with a high unemployment rate; however, the country’s manufacturing sector is one of the sectors that have been linked with job creation. Nevertheless, the growth in manufacturing production may not increase employment opportunities if this sector continues to shift to technology-intensive methods of production, which displace labour. This study uses a vector autoregressive (VAR) model to estimate the interaction between manufacturing production and the employment rate in South Africa from 1970 to 2013. Results revealed that both variables were stationary at the first difference and there was a long-term equilibrium relationship between the variables. In the short term, a significant positive relationship between manufacturing production and employment rate was observed. Granger causality test showed that there is a causal link from manufacturing production to the employment rate. A comparison between apartheid and post-apartheid periods showed the long-run relationship only existed in the post-apartheid period of a more open economy. Findings of this study revealed that a growth in the South African manufacturing sector is linked with employment opportunities in the short-run. However, these opportunities may be reduced by changes in technology which promote capital intensive production. As such, policy-makers should encourage policies that promote a mix of labour and capital intensive production in order to maintain these employment opportunities in the manufacturing sector.